2021
DOI: 10.3390/cells10010108
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Antigen xCT and Mutant-p53 as Molecular Targets for New Combinatorial Antitumor Strategies

Abstract: The cystine/glutamate antiporter xCT is a tumor-associated antigen that has been newly identified in many cancer types. By participating in glutathione biosynthesis, xCT protects cancer cells from oxidative stress conditions and ferroptosis, and contributes to metabolic reprogramming, thus promoting tumor progression and chemoresistance. Moreover, xCT is overexpressed in cancer stem cells. These features render xCT a promising target for cancer therapy, as has been widely reported in the literature and in our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 131 publications
2
21
0
Order By: Relevance
“…In the present study, we found that propofol improved the antioxidant capacity of cardiomyocytes by improving the levels of FTH1, XCT, or GPX4 and reducing iron levels. Another study has shown that p53 inhibits cysteine absorption by downregulating XCT expression ( Magri et al, 2021 ), resulting in the inhibition of cystine-dependent glutathione oxidase activity and increased cell lipid ROS, leading to ferroptosis ( Jiang et al, 2015 ). Our results showing propofol downregulation of p53 and reduction of cardiomyocyte dysfunction are consistent with the previous study ( Lai et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that propofol improved the antioxidant capacity of cardiomyocytes by improving the levels of FTH1, XCT, or GPX4 and reducing iron levels. Another study has shown that p53 inhibits cysteine absorption by downregulating XCT expression ( Magri et al, 2021 ), resulting in the inhibition of cystine-dependent glutathione oxidase activity and increased cell lipid ROS, leading to ferroptosis ( Jiang et al, 2015 ). Our results showing propofol downregulation of p53 and reduction of cardiomyocyte dysfunction are consistent with the previous study ( Lai et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The SXC inhibitor also synergizes with PRIMA-1 in vitro to lower GSH levels in non-small lung cancer H2199 cells with mutant p53 [ 38 ]. These studies, and ours, suggest that PRIMA-1 Met may be an attractive candidate for targeting the intracellular effects of xCT by impairing cancer stem cell antioxidant defense mechanisms [ 43 ]. However, although we did use the more lipophilic, methylated version of this small molecule, our intracranial study ( Figure S2 ), in combination with previous work [ 28 ], suggests that PRIMA-1 Met may have poor blood–brain barrier permeability.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, mutant p53 protein is endowed with the capability to induce a transcriptional downregulation of xCT with concomitant induction of ferroptosis. In this review the authors described the direct and indirect pathways between p53 and xCT, to be employed for new combination cancer therapies based on the use of mutant forms of p53 together with xCT [25].…”
Section: Other Therapeutic Approaches For Cancer Abolitionmentioning
confidence: 99%